(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Hepatobiliary cysts consist of a heterogeneous group of diseases that differ in cause, prevalence and manifestations. Some are found incidentally on imaging studies and tend to have a benign course. Symptomatic cysts and those become endanger to life need adequate treatment. We are reporting clinical and pathological features of 145 patients with different types of Hepatobiliary cysts along with their therapeutic approaches and outcomes. Study period was September 1997 to July 2006 (107 months). The most common was simple cyst followed by hydatid and choledochal cysts. Fifty-four (37.25%) cysts were asymptomatic and diagnosed incidentally, 75 (51.72%) had some form of symptoms; like abdominal pain, discomfort and swelling. Complications like obstructive jaundice; portal hypertension, vena caval obstruction, bronchobiliary fistula and peritonitis are noted in remaining 16 (11.03%) symptomatic patients. They were treated by partial pericystectomy with omentoplasty (44.83%), excision of the cyst with Roux-en-Y Hepaticojejunostomy or Cholangiojejunostomy (16.55%), partial pericystectomy with closure of the biliary leakage and omentoplasty (13.8%), closed total cystectomy (5.52%), right or left typical or atypical hepatectomy (14.49%), segmental deroofing and fenestration (4.8%). There were no operative deaths or major postoperative complications. The recurrence was documented in 7 patients (4.83%) in the follow up period. Three patients with hepatobiliary cystadenocarcinoma died during follow-up. In summary, Clinico-pathological features, therapeutic approaches and outcome of 145 Hepatobiliary cysts after surgery has been discussed in the light of published literatures. DOI: 10.3329/jbcps.v27i1.4238 J Bangladesh Coll Phys Surg 2009; 27: 13-21